Highly Efficient Autologous HIV-1 Isolation by Coculturing Macrophage With Enriched CD4+ T Cells From HIV-1 Patients - Xufré, Cristina; González, Tanía; Leal, Lorna; Trubey, Charles M.; Lifson, Jeffrey D.; Gatell, José María; Alcamí, José; Climent, Núria; García, Felipe; Sánchez-Palomino, Sonsoles (Frontiers in Virology, 2022)
We described a novel HIV autologous isolation method based in coculturing macrophages and CD4+T-cell-enriched fractions from peripheral blood collected from antiretroviral-treated (ART) HIV patients. This method allows the isolation of high viral titers of autologous viruses, over 1010HIV RNA copies/ml, and reduces the time required to produce necessary amounts for virus for use as antigens presented by monocyte-derived myeloid cells in HIV therapeutic vaccine approaches. By applying these high titer and autologous virus produced in the patient-derived cells, we intended to elicit a boost of the immunological system response in HIV therapeutic vaccines in clinical trials.